Dojrzałość psychiczna i społeczna oraz nastawienie wychowanków na skuteczne działanie jako miara sukcesu edukacyjnego - Chmiel, Izabela; Górkiewicz, Maciej; Kopyt, Elżbieta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Evaluation procedures in education are crucial to both individual improvement and organizational efficacy. Alas, at the present time nobody can predict what skills and what professions will be advantageous after next 10 and more years. In a such situation we recognize the need for including to evaluation systems the student’s psychical and social development, and the growth of ability to cooperate with others. The purpose of this study was to evaluate the psychometric properties of the Emotional Intelligence Questionnaire (INTE) and the General Self-Efficacy Scale (GSE) in a population of Polish nursing students. A convenience sample was recruited from the first course students, and a total of 67 participants completed the INTE, GSE and a demographic questionnaire at the end of the course. The internal consistency was confirmed with Cronbach’sα=0,89 for INTE and α=0,98 for GSES. High correlation between GSE and INTE, equal to R=+0.72, indicates the satisfactory external validity of these scales. The findings from pilot research confirmed usefulness of the proposed approach and the need of the further research.
Keywords: edukacja; GSES; INTE; inteligencja emocjonalna; skuteczność własna; systemy ocen